Efforts to Increase Congregational Commitment Using a Customer Relationship Management Approach - L., Richard Alexander; Hartini, Sri (ARRUS Journal of Social Sciences and Humanities, 2023)
GKI Gresik, which is experiencing a decrease in the number of church attendance visits for worship. After the Covid-19 pandemic changed individual behavior in carrying out onsite activities. Currently, several congregations are switching their worship activities online. So it also affects the attendance of the congregation to carry out activities or worship at the church. In 2021 there will be a slight increase because he will be allowed to return to worship in person. The authors used qualitative field research and analytical description methods in this study. In collecting data, the researcher used a questionnaire to six sample congregations who were consumers of the services provided by the church. Improving services to congregations and sympathizers in the realm of management knowledge is included in CRM (Customer Relationship Management) theory. People, processes, and technology can influence customer satisfaction (congregation). Of course, at this time, it is very appropriate if the church can adopt it to maintain and even increase the congregation's commitment.